Assessment of self-efficacy to employ self-initiated pornography use-reduction strategies. (January 2015) - Kraus, Shane W.; Rosenberg, Harold; Tompsett, Carolyn J.
Abstract: Introduction : This study evaluated several psychometric properties of a newly developed questionnaire designed to assess individuals' self-efficacy (from 0% to 100%) to employ self-initiated cognitive–behavioral strategies intended to reduce the frequency and duration of their pornography use. Methods : Using a web-based data collection procedure, we recruited 1298 male users of pornography to complete questionnaires assessing hypersexuality, pornography use history, and general self-efficacy. Results : Based on a principal component analysis and examination of inter-item correlations, we deleted 13 items from the initial pool of 21 strategies. The resulting 8-item questionnaire had excellent internal consistency reliability, and a moderate mean inter-item correlation considered indicative of unidimensionality. In support of criterion validity, self-efficacy to employ use-reduction strategies was significantly associated with the frequency with which participants used pornography, with scores on a measure of hypersexuality, and with the number of times one had attempted to cut back using pornography. In support of discriminant validity, we found that pornography use-reduction self-efficacy scores were not strongly correlated with general self-efficacy. Conclusions : Both researchers and clinicians could use this questionnaire to assess pornography users' confidence to employ self-initiated strategies intended to reduce the duration and frequency with which they use pornography. Highlights: New questionnaire assesses self-efficacy to use pornography reduction strategies. Use-reduction self-efficacy varied by weekly frequency of pornography use. Associations with other constructs supported criterion and discriminant validity. Questionnaire has clinical applications for assessment and treatment.